PENGARUH SIZE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE: STUDI KASUS PADA SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2016-2019 - Dewinda Amalia Syahputeri; Teguh Erawati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
Taxes are the biggest income for the State. But on the other hand, the company considers taxes to be a burden that can reduce corporate profits. Due to these differences, companies take advantage of loopholes in the Act to carry out tax evasion. This study aims to determine and analyze the effect of size and CSR on tax avoidance. The nature of this research uses quantitative and the data used is secondary data with the sampling technique using purposive sampling. This study uses manufacturing companies in the consumer goods sector listed on the IDX in 2016-2019 as samples. Based on this method, 18 companies were obtained. The results of this study indicate that CSR has no effect on tax avoidance, while company size has a negative effect on tax avoidance.